Composición florística y estructural del bosque secundario de regeneración natural en la finca "MUROCOMBA" propiedad de la UTEQ, año 2020. - Molina Gruezo, Joao Alejandro (2020)
This research was carried out in the secondary forest of the "Murocomba" farm owned by UTEQ, located in the canton of Valencia, province of Los Ríos. The objective was to evaluate the floristic composition and structure of the secondary forest of natural regeneration in the farm "Murocomba". Five random sampling units of 400 m2 were established. In each plot, an inventory of trees with a DBH ≥ of 7.5 cm was made, recording the common name, characteristics and height of the species. Diversity, dominance and similarity indices were evaluated, as well as the Importance Value Index (IVI) and Forest Value Index (IVF). A total of 137 individuals belonging to 14 families, 16 genera and 17 species were found, the most important families being Meliaceae with 4 species. The Importance Value Index (IVF) indicated that, the most representative species were Henriettella tuberculosa (colca) with 38.34%; followed by the species Aegiphila alba (lulo), with 9.49% and Toxicodendron striatum (aluvilla) with 8.21%. The most important species for the forest value index (FVI) was Aegiphila alba (lulo) (13.95%), because it was one of the species with the largest diameter (≥ 50 cm) found in the area. Shannon's highest diversity index was 2.13, indicating that plot 5 had a high species diversity, while Simpson's dominance index was 0.866, showing that plot 5 had the highest dominance, while Jaccard's similarity index between sampling units 2 and 3 indicated 50% similar species. In the diameter distribution, the largest number of individuals (89) were concentrated in the diameter class II (10 - 20 cm). The general distribution shows the shape of the J-curve inverted by the recovery process in the remnant and the sociological position of the heights among the specimens did not exceed 25 m in height. According to the Species Enrichment Plan, viable and sustainable strategies were created, which can be implemented in the forest, bringing economic, protection and conservation benefits. ABSTRACT Keywords: Floristic composition, regeneration, species, indexes, enrichment plan.